Iowa RBA, December 7, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for December 7, 1998. Highlights include Bohemian Waxwing, Surf Scoter, Black-legged Kittiwake, and Thayer's Gull. Includes notes for updates for December 10, and December 12. Epson - sheet feed/flatbed